Chapter 1 The Nature of Accidents - Green, Steven D. (Taylor & Francis, 2023)
"The capable and competent pilot will never allow an airplane to crack up..." is an axiom from early flight training guidance, and to some extent still informs our perception of aviation safety. It established a linear, cause-and-effect model, which coincidentally fits nicely with the narrative mode of thought, telling a story that is comprehensible. The linear model is also convenient for much of historical and contemporary management theory, which is largely aimed at controlling information, managing stories and establishing certainty. In fact, aviation operations, technology and the operating environment are inherently complex, introducing persistent vulnerability. Not only will the pilot never see the accident coming that actually happens, but he or she will also never see all of the potential accidents that could have happened but did not. A different approach must be articulated. This approach utilizes strategy, prudence, mindfulness, and particularly the assertive protection of the margins to manage uncertainty, persistent vulnerability and ultimately facilitate a "dynamic non-event".